(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2026)
This study examines how press releases (PRs) are used and how they could be improved during the journalistic production process. A sample of 322 PRs published in the EurekAlert! repository was examined through content analysis, complemented by a sociotechnical approach and observation of journalistic production practices. The findings indicate that churnalism (the full or partial reproduction of the original text) is prevalent: one in four PRs was reproduced ipsis litteris (verbatim), one in two underwent minor alterations, and one in five received complementary additions that increased its journalistic value. The analysis reveals an inverse relationship between the laboriousness of a strategy and its frequency of use. This is evidenced by the less frequent application of more demanding techniques, such as: interviewing researchers not directly involved in the reported work, citing caveats, or warning that results announced at conferences are merely abstracts of ongoing studies. Expanding upon these results, the theoretical and practical framework suggests nine possibilities for enriching journalistic stories based on PRs. These possibilities emphasize the inclusion of actors beyond those directly involved in the research, highlighting their connections and the uncertainties regarding the results and the continuation of the scientific work.